PEMANFAATAN VIDEO CONFERENCE PADA PEMBELAJARAN SENI TARI KREASI SISWA KELAS XI SMA MUHAMMADIYAH 1 PALEMBANG - Maharani, Amelia; Yelli, Nofroza; Putra, Rio Eka (Besaung : Jurnal Seni Desain dan Budaya, 2021)
The problem in this study is "How to use video conferencing in learning the art of creative dance for students of class XI SMA Muhammadiyah 1 Palembang, with the aim of describing the results of learning dance creations using video conferencing for class XI students of SMA Muhammadiyah 1 Palembang starting from planning, implementing, and evaluating learning . The benefit of this research is to increase insight and understanding of learning, especially about the art of creative dance through the use of video conferencing provided by educators to class XI students of SMA Muhammadiyah 1 Palembang. This research was conducted using qualitative methods with data collection techniques of observation, interviews and documentation. After data collection is done, the results of research and discussion can be concluded which can be concluded that the use of video conferencing in creative dance learning is very helpful in the distance learning process. In this study, the creative dance learning process went well, which can be seen from the description of the implementation of learning to evaluation, interviews with teachers and class XI students of SMA Muhammadiyah 1 Palembang, as well as documentation related to the results of evaluations carried out by teachers to students regarding the material that has been given using video conferencing.